OPTICAL AND ELECTRICAL-PROPERTIES OF TITANIUM-DIOXIDE FILMS WITH A HIGH MAGNITUDE DIELECTRIC-CONSTANT GROWN ON P-SI BY METALORGANIC CHEMICAL-VAPOR-DEPOSITION AT LOW-TEMPERATURE - KIM, TW; JUNG, M; KIM, HJ; PARK, TH; YOON, YS; KANG, WN; YOM, SS; NA, HK (AMER INST PHYSICS, 1994)
Metalorganic chemical vapor deposition of titanium dioxide (TiO2) on p-Si(100) using titanium isopropoxide and nitrous oxide via pyrolysis at relatively low (approximately 500-degrees-C) temperature was performed to produce high quality TiO2/p-Si interfaces and to fabricate TiO2 insulator gates with a dielectric constant of high magnitude. Scanning electron microscopy shows that the surfaces of the TiO2 films have very smooth morphologies. From the x-ray diffraction analysis, the grown layer was found to be a polycrystalline film. Raman spectroscopy showed the optical phonon modes of a TiO2 thin film. The stoichiometry of the TiO2 film was investigated by Auger electron spectroscopy. Room-temperature current-voltage and capacitance-voltage measurements clearly revealed metal-insulator-semiconductor behavior for the samples of the Ag/TiO2/p-Si. The interface state density at the TiO2/p-Si interface was approximately high 10(11) eV-1 cm-2 at the middle of the Si energy gap, and the dielectric constant determined from the capacitance-voltage measurements was as large as 73. These results indicate the TiO2 layers grown at relatively low temperature can be used for high density dynamic memory.
Keywords: TA2O5 FILMS; THIN-FILMS; SILICON; INP